Seasonal winter forecasts and the stratosphere. (25th October 2015) - Scaife, A. A.; Karpechko, A. Yu.; Baldwin, M. P.; Brookshaw, A.; Butler, A. H.; Eade, R.; Gordon, M.; MacLachlan, C.; Martin, N.; Dunstone, N.; Smith, D.
Abstract: We investigate seasonal forecasts of the winter North Atlantic Oscillation (NAO) and their relationship with the stratosphere. Climatological frequencies of sudden stratospheric warming (SSW) and strong polar vortex (SPV) events are well represented and the predicted risk of events varies between 25 and 90% from winter to winter, indicating predictability beyond the deterministic range. The risk of SSW and SPV events relates to predicted NAO as expected, with NAO shifts of −6.5 and +4.8 hPa in forecast members containing SSW and SPV events. Most striking of all is that forecast skill of the surface winter NAO vanishes from these hindcasts if members containing SSW events are excluded.